Singing in the Fire: Stories of Women in Philosophy - Alcoff, Linda Martín (Rowman & Littlefield Publishers, 2003)
Ask most people to imagine a philosopher and they probably think of someone like Socrates—absent-minded, perhaps, but with a sharp intellect and a thirst for the truth. A woman juggling car pools and housework is not the first image that springs to mind, but women have taken huge steps in the philosophy profession over the past 50 years. Still, to this day, well-established women philosophers continue to face sexism from colleagues and students. Singing in the Fire is a unique, groundbreaking collection of autobiographical essays by leading women in philosophy. It mines the experience of the generation that witnessed, and helped create, the remarkable advances now evident for women in the field. These women are leaders and innovators, looking back on how they have been treated, how they might have done things differently, and how we might make progress in future generations.